Designing An instrument to measure explicit and implicit learning processes - Zólyomi, Anna (Central European Journal of Educational Research, 2020)
In this research paper, the researcher’s intention was to design an instrument that is able to measure learning under two different conditions: explicit and implicit learning. Exploring explicit and implicit learning is gaining more and more attention nowadays in the field of second language acquisition (SLA). The Quantitative method was used in this study to investigate which learning mechanism proves to be more efficient in the selected sample. The present study involved Hungarian technical school, secondary school, and university students from Budapest (N = 40) who participated in completing an Artificial Grammar Learning (AGL) task. The most important finding of the present research endeavour is that implicit learning has proven to be more effective than explicit learning in the case of the selected participants and this was a statistically significant finding. The pedagogical implication of this study is that the effectiveness of implicit learning should be reconsidered by EFL teachers in Hungary.